1990
DOI: 10.1111/j.1471-4159.1990.tb04184.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Central Nervous System Oligosaccharide Storage in Caprine β‐Mannosidosis

Abstract: Goats affected with beta-mannosidosis, an autosomal recessive disease of glycoprotein metabolism, have deficient activity of the lysosomal enzyme beta-mannosidase along with tissue storage of oligosaccharides, including a trisaccharide [Man(beta 1-4)GlcNAc(beta 1-4)GlcNAc] and a disaccharide [Man(beta 1-4)GlcNAc]. CNS myelin deficiency, with regional variation in severity, is a major pathological characteristic of affected goats. This study was designed to investigate regional CNS differences in oligosaccharid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Another study confirmed that oligosaccharide accumulates in the regional CNS in caprine β-mannosidosis. 28 These findings clearly link the prenatal lesions of the optic nerve and regional CNS in β-mannosidosis to ocular motor phenotypes such as infantile nystagmus in goats. Genetic inactivation of the MANBA gene in mice, however, did not show signs of lysosomal storage in neuronal tissues or β-mannosidosisrelated phenotypes, 29 suggesting a compensatory mechanism that might be specific to the mouse.…”
Section: Discussionmentioning
confidence: 92%
“…Another study confirmed that oligosaccharide accumulates in the regional CNS in caprine β-mannosidosis. 28 These findings clearly link the prenatal lesions of the optic nerve and regional CNS in β-mannosidosis to ocular motor phenotypes such as infantile nystagmus in goats. Genetic inactivation of the MANBA gene in mice, however, did not show signs of lysosomal storage in neuronal tissues or β-mannosidosisrelated phenotypes, 29 suggesting a compensatory mechanism that might be specific to the mouse.…”
Section: Discussionmentioning
confidence: 92%
“…Some areas that were vacuolated did not show increased expression, and some regions with higher expression (e.g., Purkinje cells in cerebellum) did not show vacuolation. In general, b-mannosidase has very low expression throughout the CNS in mice (Lein et al 2007) and in goats (Boyer et al 1990;Lovell et al 1994) compared to that of other glycoprotein catabolic enzymes. There is no apparent consistent correlation among gene expression, enzyme activity, and severity of vacuolation.…”
Section: Discussionmentioning
confidence: 99%
“…The storage material does not stain with PAS and appears clear in electron microscopic examination. Regionally specific myelin deficiency is present in the CNS but not in peripheral nerves Lovell and Jones 1983;Boyer et al 1990). In contrast with ruminant b-mannosidosis, human cases have a milder and heterogeneous clinical expression, even when caused by functionally null mutations (Alkhayat et al 1998;Bedilu et al 2002;Cooper et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…This and other results indicate that the deficit arises from direct effects on oligodendroglial dif ferentiation and myelination rather than secondarily due to abnormal axonal development. There is no evidence for toxic effects of the accumulated substrates [7,8], but hypothyroidism has been hypothesized to contribute to dysmyelination [9]. As one approach toward examining the effects of this enzyme defect on myelination and the basis for regional variation, we have analyzed levels of the oligodendroglial proteins myelin basic protein (MBP) and proteolipid protein (PLP) in spinal cord, brainstem and cerebral hemispheres of normal and affected goats.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is no suggestion of delayed onset of myelination or recovery with increasing age after birth. Also, in compar ing brain and spinal cord, there is no correlation between the extent of accumulation of trisaccharide and the sever ity of myelin deficits [7], One explanation for the deficits could be a progressive decrease in an essential systemic factor. It has been hypothesized that hypothyroidism in affected goats contributes to the altered myelination [9], Decreases in thyroid hormone at birth have been docu mented, and progressive impairment of thyroid hormone production during gestation due to metabolic abnormali ties or increasing lysosomal storage could lead to severer impairment of myelination in later-developing regions.…”
mentioning
confidence: 99%